Top-down meets bottom-up: organized donor–acceptor heterojunctions for organic solar cells - Wang, Mingfeng (2013)
Solar cells involving organic small molecules and polymers have attracted intense attention from chemists, physicists and materials scientists in the past decade. Efforts in materials synthesis and device processing have led to significant improvement of the power conversion efficiency, approaching 10%. In organic solar cells (OSCs), the morphology and the interface of the donor–acceptor (D–A) heterojunctions play a critical role in determining the device efficiency. In this article, we highlight recent progress on both materials synthesis and self-assembly and lithography techniques toward ordered nanostructures and well-defined D/A interfaces that are expected to enhance the performance of OSCs.